Neuropsychology of Cognitive Functions Related to Pro-Environmental Behavior - Serra Şandor (Psikiyatride Güncel Yaklaşımlar, 2024)
The daily habits and behaviors of modern society people harm the environment more than expected. It is well known that in order to protect the inherent values of the natural assets of the world we live in, and to sustain the mutual interaction of people with the environment in a productive manner, necessary precautions should be taken to establish and maintain pro-environmental behaviors. However, people act in different levels of pro-environmental behavior. Although most of the people state that they have a pro-environmental attitude, they cannot transform their attitudes into actual behaviors in their daily lives for various reasons. Examining the mechanisms underlying this phenomenon, known as the attitude-behavior gap, may contribute to the development of interventions that can help to understand how these behaviors differ among individuals and to eliminate this difference between the observed pro-environmental behaviors. At this point, neuroscience studies can provide a more comprehensive explanation of the reasons for the behavioral differences between these individuals, by comparing the performance of individuals with and without pro-environmental behaviors and those who have adopted and not adopting the environmentalist view, on behavioral tasks, and by simultaneously examining the physiological responses that may be related to sustainable behavior. This article will discuss how neuroscience and neuropsychological approach can provide an explanation for these questions through their unique methods.